As características elementares e peculiares no mangá Naruto: abordagens sobre os aspectos históricos, culturais e mitológicos do Japão - Abreu, Sayure Souza de (Brasil, 2020)
This research has as object of study the manga Naruto, by Masashi Kishimoto, in the Brazilian version, which plot narrates the trajectory of Naruto Uzumaki to become the greatest chief of his village (Hokage) and to be recognized.The objective is to identify and analyze the elementary and peculiar characteristics that are found in the work related to approaches on the historical, cultural and mythological aspects of Japan. It is a bibliographic research, based on the theoretical foundation, the precepts of Sonia Bibe Luyten in her book Manga: the power of Japanese comics in which it categorizes the manga as being "[...] an important form of expression and capture that goes beyond any national and cultural boundaries or limits." It was verified in the work, the richness of the development of the narrative that makes a miscellany of references not only to the aspects related to Japan, but also to the cultures of other countries, configuring as being a manga with unique characteristic in its narrative.